Exploring Family Values and Female Characters in "Days Gone By" By Abdulla Kadiriy and "Almost Heaven" By Judith Mcnaught (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the exploration of family values and female characters in two distinct literary works, "Days Gone By" by Abdulla Kadiriy and "Almost Heaven" by Judith McNaught. Through a comparative analysis, the study examines how family dynamics and the portrayal of female characters contribute to the overarching themes of love, relationships, and societal norms in these novels. Ultimately, this comparative analysis offers insights into the diverse perspectives on family values and female characters presented in these two compelling literary works.